Multiphysics simulation of an anisothermal reactive spontaneous capillary rise between electric rotor wires - Moisy, Amélie; Comas-Cardona, Sébastien; Désilles, Nicolas; Genevée, Pascal; Kolehmainen, Jere (Frontiers in Materials, 2023)
The rotor is the mobile part of an electric motor. The wound rotor is mainly composed of a steel core wound by insulated copper wires. Then the winding is immersed into a liquid acrylate-based thermosetting resin bath which role is to ensure the performance and durability of the motor. The resin impregnation between the wires occurs under controlled temperature settings to facilitate the resin flow and polymerization. This process does not involve any pressurization to facilitate the resin flow between the wires. This suggests that capillary and gravity forces play a significant role on the impregnation. The global objective is to evaluate the impregnation quality. It requires to characterize and simulate a multi-materials and multi-physics process in which heat transfer, polymerization kinetics and resin flow are strongly coupled. This paper presents a fully coupled macroscopic multiphysics simulation of a unidirectional thermo-regulated capillary rise set-up. The modeling choices made enable to obtain good agreements with the experimental data and to explain a sudden change of regime observed at 120°C, due to the polymerization and thermal gradients and their impact on fluid dynamics.